Strategi Manajemen Pengembangan Sumber Daya Manusia Dalam Meningkatkan Keunggulan Kompetitif Di Pondok Pesantren Baitul Abidin Kota Batu - Arif Irvan; Abdul Kodir Djaelani; M. Khoirul ABS (E-JRM : Elektronik Jurnal Riset Manajemen, 2020)
Abstract Pesantren as an institution based on the quality of Islamic education, in practice can survive its existence which will continue to be viewed positively by the community. Pesantren currently has real local conditions that cannot keep up with the times. The regeneration factor of Human Resources (HR), which does not indicate the condition of pesantren, among them can be said that they are "reluctant to die". The existence of a period that will be experienced by modern times, pesantren will not be attractive to many people because of an assumption that the quality of education is considered less advanced. This research was conducted to analyze Baitul Abidin Islamic Boarding School (PPBA) in Batu City by using SWOT Analysis. The method used is a qualitative method. While the data collection techniques used interviews, documentation, observation and kuesioner in PPBA to find out the truth of the research data sources. PSDM Strategy at PPBA: Determine the needs, determine advice, determine the program, the implementation of the program, evaluation of the implementation of the program. Based on the SWOT Analysis, it can be known precisely the strategy that will be taken for PSDM. Strength score = 0.65 weakness = 1.27 chance = 1.20 threat = 1.75. Keywords: Human Resources Development, Swot Analysis